A thinker - Ahmad Al-Fargani - Umarov, Muhammadkadir (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article describes the activities of Al-Fargani. the author, based on published articles, made generalizing conclusions about the activities of this person